The Impact of Third Party Funds, Loan To Deposit Ratio And Capital Adequacy Ratio On Return On Assets: Case Study of Banking Listed on the IDX 2018-2022 Period - Arif, Bahtiar; Priono, Putriasyahwa Nurezky; Suardy, Weman; Azhar, Zul (Jurnal Ilmiah Manajemen Kesatuan, 2024)
This research aims to determine whether Third Party Funds, Loan to Deposit Ratio, and Capital Adequacy Ratio have a partial and simultaneous effect on Return On Assets. The population in this research is banks registered on the Indonesia Stock Exchange for the period 2018 - 2022, totaling 45 banks, then the sample was determined using the Purposive Sampling method so that a sample of 7 banks was obtained. The analytical methods used are the classical assumption test, multiple linear regression analysis test, t test, f test, and coefficient of determination test. Data testing was carried out using IBM SPSS Statistics 27 Software. The results of this research show that: 1) Third Party Funds partially have a significant effect on Return on Assets. If Third Party Funds experience an increase, this will be followed by an increase in Return On Assets. 2) Loan to Deposit Ratio partially has a significant effect on Return on Assets. A high LDR ratio can cause banks to earn greater profits as loans increase. 3) Capital Adequacy Ratio partially has a significant effect on Return on Assets. A high CAR indicates that the bank has sufficient capital to cover risks that may arise from its operational activities. 4) Third Party Funds, Loan to Deposit Ratio and Capital Adequacy Ratio simultaneously have a significant effect on Return On Assets with a coefficient of determination of 52.2%. Keywords: Third Party Funds, Loan to Deposit Ratio, Capital Adequacy Ratio, Return On Assets